Stem cell-based therapeutic strategies for cartilage defects and osteoarthritis. (June 2018) - De Bari, Cosimo; Roelofs, Anke J
Highlights: ACI is the gold standard cell therapy for cartilage defect repair. MSCs are promising substitutes for chondrocytes in ACI-like procedures. Intra-articular MSC delivery for OA is safe but efficacy remains to be established. Extracellular vesicles could replace cells in therapy. Understanding endogenous repair mechanisms could lead to targeted therapies. Abstract : The gold standard cell therapy for repair of articular cartilage defects is autologous chondrocyte implantation, with good outcomes long-term. Mesenchymal stromal/stem cells (MSCs) from bone marrow or connective tissues such as fat are being pursued as alternatives for cartilage repair, and are trialled via intra-articular administration in patients with knee osteoarthritis. Early-phase clinical studies concur on safety and provide some promising insight into efficacy, but the mechanism of action remains unclear. Recent studies implicate extracellular vesicles as important mediators of MSC action, offering exciting therapeutic prospects. Our increasing understanding of the mechanisms underlying intrinsic articular cartilage maintenance and repair fosters hope that novel/repurposed therapeutics could elicit repair through activation of endogenous stem/progenitor cells to maintain healthy joints and prevent osteoarthritis.